PERBEDAAN KETINGGIAN TEMPAT TERHADAP PERTAMBAHAN BOBOT BADAN KAMBING PERANAKAN ETAWA (PE) JANTAN LEPAS SAPIH - Nita Opi Arikustanti (AVES: Jurnal Ilmu Peternakan, 2016)
Etawa Cross Goat (PE) is a kind of a goat. It is a cross breed between Etawa and Kacang goat. Climate, Temperature and Humidity are the important factors to increase the weight of a goat. Some kinds of goat are spread in a mountain range or plateau because the goat is like it. Problem of research is the effect of different site in increasing the weight of weaned male Etawa Cross Goat. Objective of study: To investigate the effect of different site to the weight of weaned male Etawa cross Goat. Method of study: This study is using Experimental design. It is intended to find out the effect of different site to the weight of weaned male Etawa Cross Goat. The technique of data analysis is using T-Test. The finding of study was that the t count = (0,11). Standard deviation of the goat on the plateau is and the standard deviation on the goat on lowland is. This means that there was not significant different weight of weaned male Etawa Cross goat which is live on plateau and on lowland.Key words: Etawa Cross Goat, Different Site, Animal Weight